Kajian Film Dokumenter “Yang Diperas Cuciannya, Bukan PRT-nya” (2024) dalam Pendekatan Pekerjaan Sosial Feminis - Tamba, Wahyu Pratama; Nugroho, Fentiny (JOM, 2024)
This research aims to review the problems of domestic workers presented in the documentary film "Yang Diperas Cuciannya, Bukan PRT-nya" and analyze the factual problems of domestic workers from a feminist approach in the context of social work intervention. This approach focuses on addressing gender injustice and inequality with the aim of empowering women. Female domestic workers experience acts of violence, sexual harassment, lack of work and legal protection and social security. Therefore, the ratification of the Draft Law on the Protection of Domestic Workers is needed as an effort to improve the protection and welfare of domestic workers. This qualitative approach research uses descriptive research. Interpretation and analysis of research data comes from the content of the documentary film "Yang Diperas Cuciannya, Bukan PRT-nya" and is supported by a literature review. The literature review shows that previous research discusses several things including ideas, the historical context of feminism globally and in Indonesia, and gender inequality in various fields of life. Substantially, the feminist perspective helps everyone build knowledge in treating and positioning women in the social structure of life and builds awareness of the challenges of injustice experienced by women.